Evaluation of Proximate Composition and Glycemic Indices of Ten Maize Varieties Indigenous to Pakistan - Aleena Naeem; Humera Fiaz; Amjad Shehzad; Abdul Rehman Khan (agriTECH, 2026)
Maize (Zea mays) is an extensively cultivated versatile cereal with essential macro and micronutrients, including dietary fibers, contributes to global food security. Therefore, this study aimed to assess the proximate composition, energy content, antioxidant potential and glycemic index evaluation of 10 maize varieties cultivated in various regions of Pakistan. The experiment was carried out using biochemical methods for proximate composition analyses, including moisture, ash, crude fat, protein, crude fibers and carbohydrate content. Antioxidant activity was assessed through ABTS and DPPH assays, while total phenolic and flavonoid contents were quantified spectrophotometrically. Glycemic Index (GI) and Glycemic Load (GL) were evaluated through controlled human trials using standardized methods. The results showed that the moisture content ranged from 9 to 12%, with M3 being the lowest and M8 was the highest. Crude fats, proteins, fibers and carbohydrates contributed to energy content ranging from 300 to 387 kcal/100 g. Furthermore, the antioxidant potential of maize varieties was assessed using ABTS and DPPH free radical scavenging assays. The ABTS assay showed 32 – 45% antioxidant activity while DPPH ranged from 18 to 35%, with M1 and M9 varieties having the highest phenolic (57 ± 1.6 mg) and flavonoid (128 ± 2.9 µg) contents, respectively. The GI values, a practical nutritional concept, ranged from 68 (M9; medium GI maize variety) to 76 (M7; high GI maize variety) with a corresponding GL between 34 and 38. This indicated that maize varieties showed great variation in proximate composition, antioxidant potential, and GI values, offering basic and valuable insights to explore various features of maize associated with dietary habits and human health conditions.